2015
DOI: 10.1111/1365-2656.12365
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between the spatial distribution of resource patches and population density: consequences for intraspecific growth and morphology

Abstract: Summary1. How individuals within a population distribute themselves across resource patches of varying quality has been an important focus of ecological theory. The ideal free distribution predicts equal fitness amongst individuals in a 1 : 1 ratio with resources, whereas resource defence theory predicts different degrees of monopolization (fitness variance) as a function of temporal and spatial resource clumping and population density. 2. One overlooked landscape characteristic is the spatial distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
1
15
1
Order By: Relevance
“…In our system, we found that high density of young fish was associated with migratory fish, a pattern that has been detected in other partially migratory populations of O. mykiss (McMillan et al 2015) and salmonid fishes (e.g., Salmo trutta, Bohlin et al 2001). Many aspects of salmonid population ecology are density-dependent; higher juvenile density reduces growth rates (Jenkins et al 1999) but increases body size variation (Jacobson et al 2015). In other species, seasonal differences in density associated with migratory individuals (pulsed, seasonal increase in densities) vs. resident individuals (year-round presence) can influence ecological dynamics.…”
Section: Density In Partially Migratory Populationssupporting
confidence: 78%
“…In our system, we found that high density of young fish was associated with migratory fish, a pattern that has been detected in other partially migratory populations of O. mykiss (McMillan et al 2015) and salmonid fishes (e.g., Salmo trutta, Bohlin et al 2001). Many aspects of salmonid population ecology are density-dependent; higher juvenile density reduces growth rates (Jenkins et al 1999) but increases body size variation (Jacobson et al 2015). In other species, seasonal differences in density associated with migratory individuals (pulsed, seasonal increase in densities) vs. resident individuals (year-round presence) can influence ecological dynamics.…”
Section: Density In Partially Migratory Populationssupporting
confidence: 78%
“…low velocity areas within riffles) may have occurred across all density levels. At low densities, individuals have been found to compete via antagonistic interactions (Brown et al , Tregenza et al , Jacobson et al ), individuals excluded to the use of alternative habitats (akin to dispersers in the resident versus disperser dichotomy in the non‐random movement/dispersal literature; Clobert et al , Edelaar and Bolnick , Bolnick and Otto ) those less specialized (i.e. adapted) and thereby less competitive (Jacob et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Since, however, a greater number of individuals were able to utilize preferred habitat at higher densities than the number found within such sections at low density, we consider habitat choice in our low density trials to be independent of competitive effects and this is the more unlikely explanation for the habitat use in these trials. In systems with high densities, individuals have been found to increasingly compete via scramble interactions as their ability to defend optimal locations decreases (Tregenza et al , Jacobson et al ). Phenotypic‐sorting thereby decreases as a function of density under this process as all adapted relatively competitive individuals are able to remain within preferred (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This feeding flexibility is an adaptive response (Brandão-Gonçalves et al, 2009) to fluctuations in the availability of food resources in the environment (Abelha et al, 2001). Such fluctuations may be caused by several factors such as physicochemical, spatial and temporal components (Lawlor, 1980;Costa et al, 2013;Jacobson et al, 2015). For example, the presence of riparian vegetation is an important source of food subsidies for fishes (Esteves, Aranha, 1999;Burnett, Reeves, 2006) as well as for shading the water (Pusey, Arthington, 2003).…”
Section: E170167[2]mentioning
confidence: 99%